Maintaining the Malay local quality of life by utilizing vernacular functional spatial features - GhaffarianHoseini, AmirHosein; Baharuddin, Mohd Nasir; Ibrahim, Rahinah (2010)
The quality of contemporary residential functional spaces has been mostly based on style and modernization rather than the tradition of particular regional context. This has led to new buildings which are not based on the tradition of their own regional context. In view of the rapid modernization of Malaysia, the kampong house as a Malay vernacular architecture has been replaced by modern architecture. We are motivated to conduct this study because we observed the increasing loss of functional spatial features of the kampong house that supports Malay local quality of life. In this research, an archival research method is conducted to study the vernacular architectural features of Malay vernacular houses. These features include spatial characteristics of functions and spaces that are based on local needs. We posit that this loss of functional spatial features is key to the diminishing quality of life for people living in contemporary houses. This research found that the vernacular functional spatial features could support the quality of life while integrated successfully into contemporary functional spaces. Consequently, these features when utilized in designing contemporary functional spaces could exude the Malay vernacular quality of life.